2023
DOI: 10.3389/fnbeh.2023.1147784
|View full text |Cite
|
Sign up to set email alerts
|

CatWalk XT gait parameters: a review of reported parameters in pre-clinical studies of multiple central nervous system and peripheral nervous system disease models

Abstract: Automated gait assessment tests are used in studies of disorders characterized by gait impairment. CatWalk XT is one of the first commercially available automated systems for analyzing the gait of rodents and is currently the most used system in peer-reviewed publications. This automated gait analysis system can generate a large number of gait parameters. However, this creates a new challenge in selecting relevant parameters that describe the changes within a particular disease model. Here, for the first time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 117 publications
1
2
0
Order By: Relevance
“…We further evaluated motor function using CatWalk gait analyses to monitor gait. Similar to previous studies, we observed increased phase dispersion (irregular placement of forepaws) and decreased coupling (asynchronous paw placement) in our stroke+vehicle mice at PSD8 (Figure 4F) [36]. Notably, stroke+NWL283 mice displayed phase dispersion and coupling that resembled their baseline values and were improved compared to stroke+vehicle (phase dispersion: stroke+vehicle = 3.64 ± 0.89% vs. stroke+NWL283 = −0.041 ± 1.21%; p = 0.048) (coupling: stroke+vehicle = −3.0 ± 0.76% vs. stroke+NWL283 = −1.0 ± 0.91%; p = 0.028) (Figure 4F).…”
Section: Discussionsupporting
confidence: 91%
“…We further evaluated motor function using CatWalk gait analyses to monitor gait. Similar to previous studies, we observed increased phase dispersion (irregular placement of forepaws) and decreased coupling (asynchronous paw placement) in our stroke+vehicle mice at PSD8 (Figure 4F) [36]. Notably, stroke+NWL283 mice displayed phase dispersion and coupling that resembled their baseline values and were improved compared to stroke+vehicle (phase dispersion: stroke+vehicle = 3.64 ± 0.89% vs. stroke+NWL283 = −0.041 ± 1.21%; p = 0.048) (coupling: stroke+vehicle = −3.0 ± 0.76% vs. stroke+NWL283 = −1.0 ± 0.91%; p = 0.028) (Figure 4F).…”
Section: Discussionsupporting
confidence: 91%
“…In addition to the classical RotaRod approach, we addressed the demand made in Plank et al (2018) to apply an additional, more sensitive method to investigate motor function and gait. The CatWalk assay can measure over 250 parameters and allows a more holistic investigation of locomotion compared to the classical RotaRod approach ( Vandeputte et al, 2010 ; Timotius et al, 2023 ). Clear differences were detected between both sexes of the F344tgHD model, as already observed with the RotaRod approach.…”
Section: Discussionmentioning
confidence: 99%
“…We used the CatWalk XT automated gait analysis system to analyze the gait of each group of rats (Noldus Information Technology, Netherlands, https://www.noldus.com/catwalk-xt ) 45 , 46 . The software name is CatWalk™ XT and version is 10.6.…”
Section: Methodsmentioning
confidence: 99%